IPCDs and Warfarin Similarly Effective for Preventing VTE After Joint Replacement - Summers, Jaye (MD Conference Express, 2015)
In a prospective trial among patients who underwent elective total knee or hip replacement, pneumatic compression devices and warfarin were both effective in preventing thrombolic events. Bleeding events, wound complications, and drainage were significantly higher among those on warfarin. Patient satisfaction was higher among those with a pneumatic compression device.